Iron metabolism in high-altitude residents - Muckenthaler, Martina; Mairbäurl, Heimo; Gassmann, Max (Journal of applied physiology, 2020)
Residents at high altitude cope with decreasing inspiratory oxygen partial pressure by stimulating erythropoiesis. The increase in hemoglobin levels requires high amounts of additional iron supplied from the diet. Here, we review available data on how iron metabolism adapts when living in a hypoxic environment. Our analysis reveals that long-term adaptation to high altitude enables healthy individuals to maintain their iron stores within the physiological range despite elevated requirements for erythropoiesis. However, in vulnerable populations with increased iron demand (e.g., pregnant women or exercising individuals), iron stores are less likely to be replenished quickly when living at high altitude. Future studies need to address whether different ethnicities have acquired genetic mechanisms to adapt to the elevated iron demand for erythropoiesis at high altitude.